Exile and migration in La nave de los locos, by Cristina Peri Rossi : a journey to others’ spaces (2012)
In La nave de los locos, the proposed signals surrounding the topic of a ship collecting mad people, which represents a mental hospital space, concentration camps, or dictatorships, highlights their abandonment and deprivation from society and its fundame